Isolated jejunal perforation - hidden danger in blunt abdominal trauma - Doklestić Krstina; Vasin Dragan; Jovanović Bojan; Detanac Džemail; Lešević Ivana (Srpski Arhiv za Celokupno Lekarstvo, 2021)
Introduction. Isolated jejunal perforation (IJP) without any associated injuries is rare in blunt abdominal trauma (BAT). It most commonly occurs in decelerating trauma. Diagnosis of traumatic intestinal perforation may be difficult in the first hours after injury so unrecognized “missing” intestinal injuries incidences are as high as 24%. Unrecognized traumatic bowel perforation without adequate treatment leads to the intestinal leakage into the peritoneal cavity, leading to secondary peritonitis and potentially lethal complications. Case outline. We presented the case of a 43-year-old woman injured in a road traffic accident. She was admitted to emergency surgery after diagnostic procedures according to the protocol for trauma. Initial examination, and body computed tomography (CT) revealed orthopedic injuries. Daily monitoring and follow-up examinations were done, she did not complain of any discomfort nor pain in the abdomen, and there were no signs of abdominal injury. Two days after trauma, follow-up abdominal CT revealed highly suspected jejunum perforation, still without signs of pneumoperitoneum. Laparotomy was performed and diagnosis of IJP was confirmed. Bowel perforation was surgically closed in two layers, followed by drainage of septic collections, abdominal saline lavage and primary abdominal closure. The patient was discharged on the seventh postoperative day without complications. Conclusion. In the case of BAT due to severe traumatic force in patient with nonspecific clinical signs of abdominal trauma on initial clinical and radiological examination, follow-up in a short period is necessary, to detect hidden jejunal perforation. Surgery is a life-saving for those patients and treatment of these injuries usually require simple operative procedures.